Ornamental fern flora of Andaman and Nicobar Islands - Baskaran, V; Janakiram, T; Abirami, K (Indian Horticulture, 2019)
The Andaman and Nicobar Islands stretching from Arakkan Yoma in Myanmar to Sumatra in Indonesia are housed by a rare and distinct fern flora due to the favourable climate and plentiful moisture prevailing in the island. Though the Andaman and Nicobar Islands are rich in fern biodiversity they are neglected, less cultivated and underutilized. Ornamental utilization of fern flora can open up new livelihood sources for economic growth.